Correlation Between the Mosque and Traditional House Architecture in Kudus, Indonesia - Ashadi Ashadi (International Journal of Built Environment and Scientific Research, 2017)
The spread of Islam and the rise of the cigarette industry that began in the nineteenth century are two factors that influence the transformation of mosque and traditional houses in the old city center of Kudus. This study aims to find out how the correlation between the architecture of the mosque Menara Kudus and traditional houses in the city of Kudus. The object of the study is first, the mosque Menara Kudus, and secondly, the traditional house around the mosque, which is type of single and type of series. The method used is a combination of historical documentary and architectural descriptive with survey technique. The analysis should be viewed within the framework of Javanese culture. The results of the study show that in general the traditional house architecture has no significant correlation with the architecture of mosque Menara Kudus, but it has more significant correlation with traditional Javanese house architecture.